Altered nociception and morphine tolerance in neuropeptide FF receptor type 2 over‐expressing mice. (9th December 2015) - Lin, Y.T.; Kao, S.C.; Day, Y.J.; Chang, C.C.; Chen, J.C.
Abstract: Background: The neuropeptide FF system is thought to act as an anti‐opioid modulator and plays a role in nociception, morphine antinociception and dependence. Two receptor subtypes, NPFFR1 and NPFFR2, have been identified, but their respective roles in these processes remain uncertain. Methods: In the present study, the role of NPFFR2 was investigated using transgenic mice over‐expressing NPFFR2 in addition to a NPFFR2 agonist AC‐263093. Results: NPFFR2 Tg mice exhibited increased sensitivity to both mechanical and thermal noxious stimuli compared to the WT mice, while the antinociceptive effects of morphine at three different doses (6.25, 12.5 and 25 mg/kg, s.c.) were similar in both strains. The development of tolerance to morphine antinociception after chronic morphine treatment (12.5 mg/kg, s.c.; twice daily × 5 days) was attenuated in NPFFR2 Tg mice when compared to WT mice. Similarly, WT mice receiving AC‐263093 pretreatment (2.5 mg/kg, i.p.) showed attenuated morphine tolerance compared to vehicle controls. Most naloxone‐precipitated morphine withdrawal symptoms were not attenuated in NPFFR2 Tg mice, with the exception of wet dog shake that was significantly reduced. Both NPFFR2 Tg and WT mice displayed similar degree of morphine rewarding. Conclusions: Our results suggest that neuropeptide FF R2 is mainly involved in the modulation of nociception and tolerance to morphine antinociception.